Singing and suffering with the servant: second Isaiah as guide for preaching the Old Testament - Stark, David M. (Arbeiten zur Pastoraltheologie, Liturgik und Hymnologie, 2022)
Intro -- Title Page -- Copyright -- Table of Contents -- Acknowledgements -- 1. Introduction: Isaiah as Guide to Old Testament Preaching -- 1.1 The Old Testament as a Suffering Servant -- 1.2 Toward a Constructive Understanding of Old Testament -- 1.3 The Servant Songs as Old Testament Preaching Guide -- 1.4 Guiding Approach -- 2. Analysis of Old Testament Homiletics after the Shoah -- 2.1 Elizabeth Achtemeier -- 2.2 Walter Kaiser, Jr. -- 2.3 John Holbert -- 2.4 Ellen Davis -- 2.5 Rein Bos -- 2.6 Walter Brueggemann -- 2.7 Concluding Reflections -- 3. The Suffering Servant, Preaching, and Domination -- 3.1 Excursus on Preaching and Second Isaiah -- 3.2 Subverting Systemic Injustice-Isaiah 42:1-4 (5-9) -- 3.3 Empowering Testimony-Isaiah 49:1-6 -- 3.4 Resisting and Lamenting like a Holy Fool-Isaiah 50:4-9 -- 3.5 Dialoging Against Domination-Isaiah 52:13-53:12 -- 3.6 Concluding Reflections -- 4. Listening to Servant Israel: Alexander Deeg and Jewish-Christian Dialogue in Germany -- 4.1 From Conciliation to Transformation -- 4.2 Creating Space for Dialogue -- 4.2.1 Old Testament Pietism -- 4.2.2 The Old Testament and Historical Criticism -- 4.2.3 Alexander Deeg's Proposal -- 4.3 Learning from Jewish Interpretation -- 4.3.1 Imagination and Meticulousness -- 4.3.2 Messianic Interruption -- 4.3.3 Messianic Liturgy and Jewish Presence -- 4.4 Dialogical Preaching -- 4.4.1 Preaching as Disruption -- 4.4.2 Preaching as Initiation -- 4.4.3 Preaching as Staging -- 4.4.4 Dialogical Preaching -- 4.5 Sermon Sample: "O du fröhliche…" -- 4.6 Concluding Reflections on Listening to Servant Israel -- 5. Preaching in the Presence of Domination: African American Homiletics and the Old Testament -- 5.1 Toward the Good News of the Old Testament -- 5.1.1 Exodus -- 5.1.2 Exile -- 5.1.3 Ethiopia -- 5.1.4 Emmanuel -- 5.2 Toward a Theology for Old Testament Preaching.